1991
DOI: 10.1097/00000658-199106000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Choledochoduodenostomy Analysis of 71 Cases Followed for 5 to 15 Years

Abstract: To investigate the long-term effectiveness of choledochoduodenostomy (CDD), the experience with 71 patients followed for 5 or more years after CDD was analyzed retrospectively. From 1968 to 1984, 134 patients underwent CDD. Eight patients (6%) died in the immediate postoperative period, 55 left the hospital, 8 of them were lost to follow-up, and 47 were followed but died before 5 years elapsed after CDD. The remaining 71 patients form the data base for this analysis: 38 were followed for more than 5 years, 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 22 publications
3
30
0
1
Order By: Relevance
“…12,13,16 Surgical procedures such as bile duct exploration and sphincteroplasty, and drainage procedures such as choledochoduodenostomy and hepaticojejunostomy, are options after failed endoscopic therapy in surgically fit patients. 41,42 In patients with previous cholecystectomy as well as in elderly patients or those with high surgical risk, endoscopic sphincterotomy and endoscopic clearance of common bile duct stones, if successful, become the definitive treatment. 43 Biliary endoprostheses have been used for biliary drainage both as a temporary measure as well as for long-term, permanent treatment.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,16 Surgical procedures such as bile duct exploration and sphincteroplasty, and drainage procedures such as choledochoduodenostomy and hepaticojejunostomy, are options after failed endoscopic therapy in surgically fit patients. 41,42 In patients with previous cholecystectomy as well as in elderly patients or those with high surgical risk, endoscopic sphincterotomy and endoscopic clearance of common bile duct stones, if successful, become the definitive treatment. 43 Biliary endoprostheses have been used for biliary drainage both as a temporary measure as well as for long-term, permanent treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This complication is rare (w1%), and can be managed with ERC/ES. 47,48 Other authors have suggested end-to-side choledochoduodenostomy as well as choledochojejunostomy as alternatives, 49 although endoscopic biliary access following these operations is nearly impossible. It should be acknowledged that laparoscopic choledochoenterostomies have also been reported anecdotally, 50 although there has been little experience with this technique.…”
Section: Choledochoenterostomymentioning
confidence: 99%
“…Most of these authors stipulate that the diameter of the CBD should be at least 16 mm for good outcomes of CDD. 4,6,7 There are specific indications for performing CDD, most of which have remained unchanged over time. It has been recommended in the treatment of multiple CBD stones, retained or residual stones following a prior biliary intervention, primary CBD stones, lower-end CBD strictures, dilated CBD with a diameter of more than 2 cm, or failure of ERCP.…”
Section: Discussionmentioning
confidence: 99%